Assessment of Cytotoxicity and Antioxidant Activities of Rice Berry Extracts for Body Cream Products - Tikapunya, Tiparat; Jumpatong, Kanlaya; Lapinee, Chaipat; Sansomchai, Pahol (Graduate School, Universitas Brawijaya, 2023)
The utilization of natural extracts as an ingredient in cosmetic products becomes a better choice for customers. Rice berry has been defined as a potential source of anti-free radical properties which is able to be formulated in cosmetic products. Therefore, the objectives of this study are 1) to investigate an antioxidant by ABTS and ABTS assays, total antioxidant compounds by phenolic and total flavonoids assays, and cell viability to fibroblast NIH3T3 (IC80) of ethanol and aqueous extracts of rice berry by MTT test, 2) to evaluate cream stability of each formulates adding different concentrations of rice berry extracts. The results showed that both extraction solvents did not show cytotoxicity to fibroblast NIH3T3 (IC80). However, the ethanol rice berry extracts exhibited a higher total phenolic compound, total flavonoid content, and anthocyanin content than the water rice berry extracts. The physical properties of each cream formulated, including rice berry extracts, showed no unacceptable properties. It can conclude that rice berry extracts have the potential to be a natural ingredient in cosmetic products after studies of the antioxidant properties, antioxidant compounds, cytotoxicity to normal fibroblast, and physical properties after being added to cosmetic cream. Keywords: Antioxidant, cream stability, flavonoids, normal fibroblasts, rice berry.